2020
DOI: 10.20527/btjpm.v2i1.1794
|View full text |Cite
|
Sign up to set email alerts
|

Bahan Ajar Berbasis Kearifan Lokal bagi Guru-Guru MGMP Bahasa Inggris Tingkat SMP Kabupaten Tanah Laut

Abstract: Bahasa Inggris di SMP berisi tentang teks singkat tentang deskripsi, naratif, dan prosedural. Idealnya, para siswa diberikan teks bahan ajar yang dekat dengan kehidupan mereka. Kearifan lokal yang ada pada daerah siswa dapat menjadi media belajar yang otentik bagi siswa. Di sisi lain, guru-guru Bahasa Inggris, khususnya pada jenjang SMP di Kabupaten Tanah Laut sebagian besar belum terbiasa mengembangkan bahan ajar yang bermuatan kearifan lokal. Kegiatan pengabdian masyarakat ini memiliki tujuan agar guru-guru … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The text types shown above can be adjusted and used by teachers in the context of local wisdom in their environment. This has been researched by Listia et al (2020) found in Tanah Laut district, where they created local wisdom-based teaching materials for students at Tanah Laut District Junior High Schools, that the usage of authentic teaching materials with local wisdom in their region is effective for learning English. Similarly, Arini's (2018) research, which applies the values of local wisdom in English learning in the city of Banjarmasin, has produced tangible outcomes in both theoretical and practical aspects of preserving the values of local wisdom.…”
Section: The Importance Of Local Wisdom In Learning Englishmentioning
confidence: 99%
“…The text types shown above can be adjusted and used by teachers in the context of local wisdom in their environment. This has been researched by Listia et al (2020) found in Tanah Laut district, where they created local wisdom-based teaching materials for students at Tanah Laut District Junior High Schools, that the usage of authentic teaching materials with local wisdom in their region is effective for learning English. Similarly, Arini's (2018) research, which applies the values of local wisdom in English learning in the city of Banjarmasin, has produced tangible outcomes in both theoretical and practical aspects of preserving the values of local wisdom.…”
Section: The Importance Of Local Wisdom In Learning Englishmentioning
confidence: 99%
“…Some previous research on learning is based on local wisdom such as research conducted by (Kusuma, 2016;Sarjono, 2017;Wijaya, 2018;Verawati et al,2019;Oktariani, 2019;Prihartanti, 2020;Listia et al, 2020;Armawan, 2017;Arvianty, 2020;Nasir, 2020;Supriyono & Nita, 2017;Marhaeni, 2012). Of all the research conducted by the researchers, the average of relevant research focuses on the development of reading teaching materials and Writing based on local wisdom.…”
Section: Introductionmentioning
confidence: 99%